2022
DOI: 10.1177/1420326x221107110
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic prediction of the pre-dehumidification of a radiant floor cooling and displacement ventilation system based on computational fluid dynamics and a back-propagation neural network: A case study of an office room

Abstract: This study was carried out to solve the problem of condensation in radiant floor cooling systems. Computational fluid dynamics simulation and back-propagation neural network prediction were employed to conduct thorough research to predict the effects of the displacement ventilation dehumidification phase in an office building located in Jinan, China. The effects of the air supply temperature ( T as), air supply flow rate ( V as), air supply humidity ratio ( H as), floor temperature ( T floor), initial indoor t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…An ANN is a machine learning tool used to learn the relationship between input and output variables to predict system performance [63,64]. ANNs use many neurons in a topological structure to store and process complex information.…”
Section: Bp Neural Networkmentioning
confidence: 99%
“…An ANN is a machine learning tool used to learn the relationship between input and output variables to predict system performance [63,64]. ANNs use many neurons in a topological structure to store and process complex information.…”
Section: Bp Neural Networkmentioning
confidence: 99%
“…Radiant floor cooling has been widely studied due to its low operating noise, spacesaving design, low energy consumption, and thermal comfort [12][13][14][15]. Liu et al [16] conducted a comparative analysis of three case studies and concluded that hybrid radiant cooling systems were particularly effective in extremely hot and humid conditions, prevalent during summer.…”
Section: Introductionmentioning
confidence: 99%
“…Statistical methods tend to overfit when handling diverse influencing factors, leading to poor predictive performance of the models [4][5][6][7]. With the wide application of artificial intelligence algorithms in the prediction field [8][9][10][11], more and more scholars have started researching load-predicting methods founded on machine learning [12][13][14]. Some commonly used approaches in machine learning include artificial neural networks (ANN) [15], support vector machines [16], extreme learning machines [17], random forest (RF) [18], and regression trees [19].…”
Section: Introductionmentioning
confidence: 99%